THE STRANGLING FRUIT: GOTHIC AESTHETICS AND ECOLOGICAL ANXIETY IN JEFF VANDER MEER’S ANNIHILATION - Hussain, Adil; Akhtar, Azra; Qazi, Khursheed Ahmad (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The Anthropocene, a term marking the current geological era dominated by human activity, has become a central concern in contemporary literature, particularly in the context of ecological crises. Jeff Vander Meer’s Annihilation (2014), the first book of his Southern Reach trilogy, merges elements of ecological horror and gothic aesthetics to craft a narrative that mirrors the fears and anxieties of the Anthropocene. This paper examines how Vander Meer uses gothic tropes—haunting, decay and the uncanny—to evoke a sense of environmental trauma, critiquing humanity’s destabilizing relationship with nature. Through the mysterious and ever-changing environment of Area X, the novel explores the erasure and transformation of human presence in an unstable world. Drawing on ecocriticism, gothic theory and the works of scholars such as Timothy Morton, Johan Höglund and others, this paper demonstrates how Annihilation reflects the environmental trauma of the Anthropocene and the uncanny presence of nature’s agency. The novel highlights how ecological destruction haunts both the landscape and the human psyche, creating a narrative where horror and awe coexist in confronting environmental collapse.